Imperfect Monitoring and Impermanent Reputations - Cripps, Martin W.; Mailath, George J.; Samuelson, Larry (Econometrica, 2004)
We study the long-run sustainability of reputations in games with imperfect public monitoring. It is impossible to maintain a permanent reputation for playing a strategy that does not play an equilibrium of the game without uncertainty about types. Thus, a player cannot indefinitely sustain a reputation for noncredible behavior in the presence of imperfect monitoring.